Behavioural intention of zakat participants towards the zakat fund in Morocco - Ghaouri, Mohamed Hamza; Salina, Kassim; Othman, Anwar Hasan Abdullah; Zakariyah, Habeebullah (ISRA Research Management Centre, 2023)
Purpose―Currently, there is neither a formal zakat system nor a zakat institution in Morocco. However, in recent years, discussions have intensified regarding the establishment of a national zakat fund in the Kingdom. In this regard, the paper attempts to fill the gap by examining the factors determining the intention of Moroccans to pay their zakat obligations to the national zakat fund. Design/Methodology/Approach―The present study adopts a quantitative research design based on the theory of planned behaviour (TPB). A relevant questionnaire was designed and distributed to zakat believers in Morocco. Structural equation modelling (SEM) was used to analyse the data collected.